2018
DOI: 10.1038/s41380-018-0078-5
|View full text |Cite
|
Sign up to set email alerts
|

Large-scale mapping of cortical alterations in 22q11.2 deletion syndrome: Convergence with idiopathic psychosis and effects of deletion size

Abstract: The 22q11.2 deletion (22q11DS) is a common chromosomal microdeletion and a potent risk factor for psychotic illness. Prior studies reported widespread cortical changes in 22q11DS, but were generally underpowered to characterize neuroanatomic abnormalities associated with psychosis in 22q11DS, and/or neuroanatomic effects of variability in deletion size. To address these issues, we developed the ENIGMA (Enhancing Neuro Imaging Genetics Through Meta-Analysis) 22q11.2 Working Group, representing the largest analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

27
193
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 145 publications
(227 citation statements)
references
References 66 publications
27
193
0
1
Order By: Relevance
“…22q11.2 and 16p11.2 CNVs had large effect sizes on FC that are similar to those previously reported for structural neuroimaging measures, cognition, and behaviour 8,10,11 . In sharp contrast, there is a significant discordance between the severe clinical manifestations observed in idiopathic ASD and SZ, and the small effect-size observed in case-control studies at the FC level.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…22q11.2 and 16p11.2 CNVs had large effect sizes on FC that are similar to those previously reported for structural neuroimaging measures, cognition, and behaviour 8,10,11 . In sharp contrast, there is a significant discordance between the severe clinical manifestations observed in idiopathic ASD and SZ, and the small effect-size observed in case-control studies at the FC level.…”
Section: Discussionsupporting
confidence: 86%
“…CNVs at the proximal 16p11.2 and 22q11.2 genomic loci are among the most frequent large effect-size genomic variants and alter the dosage of 29 and 50 g enes, respectively 6,7 . They confer high risk for ASD (10-fold increase for the 16p11.2 deletion and duplication) 3 , SZ (>10-fold increase for the 22q11.2 deletion and 16p11.2 duplication) 4 , and ADHD [8][9][10][11][12] . Gene dosage (deletions and duplications) affect the same neuroimaging measures in opposite directions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous single site study of 22q11DS and youth at clinical high risk for psychosis reported this directionally opposite pattern as well [24]. This is in contrast to findings for cortical gray matter, in which 22q11DS patients with psychosis showed highly significant overlap with idiopathic schizophrenia, in terms of prominent cortical thinning in fronto-temporal regions [35]. Thus, our findings suggest that patterns of neuroanatomic overlap in 22q11DS-associated vs. idiopathic psychosis markedly differ for gray and WM, and suggest that different WM phenotypes may lead to similar downstream clinical outcomes.…”
Section: Discussionmentioning
confidence: 70%
“…Genetic association studies continue to identify both common and rare variants that impact brain structures at the gross anatomical level. [124][125][126] MRI is suited to measure gross structural traits of intracranial volume and regional phenotypes like hippocampal volume or cortical surface area and thickness. [6][7][8]74,[81][82][83] These phenotypes can be measured in large numbers of living humans at a relatively affordable cost.…”
Section: Three-dimensional Brain Imaging Beyond Mrimentioning
confidence: 99%